COVID-19. Ambulatory management during intense community transmission - Ticona Huaroto, César (2020)
The COVID-19, in the scant six months of its presence, has caused a global health crisis, with greater impact in the poorest countries. Currently, there is a better understanding of the clinic of this disease and its relationship with physiopathological phenomena; however, given the high lethality, the major focus of its management has been oriented towards the hospitalized or critical patient. This information and experience is shared in order to achieve and strengthen better care for people affected by COVID-19 from their first symptoms at home, especially at these times of extensive community transmission, where health services are seriously limited in human and material resources. The aim is to (i) avoid complications beyond those caused by the evolution of the disease itself; (ii) determine the appropriate time for patient referral to the hospital and reduce lethality; (iii) reinforce the isolation of cases; and (iv) possibly, decrease the progression to severe disease. It includes outpatient management after hospital discharge, as well as recommendations to consider if health services collapse; indications for when to discharge the patient for return to work, and highlights the importance of telemonitoring for the success of this practice in the current epidemiological context.